Digital Destinations in the Tourist Sector: A Path Model for the Impact of e-Services on Tourist Expenditures in Amsterdam - Bart Neuts; Joao Romao; Peter Nijkamp; Eveline van Leeuwen (Tinbergen Institute, 2013)
Innovations in information and communication technologies (ICT) in recent decades have had profound implications for tourism services, promotion, or distribution. We apply a Structural Equations Model (SEM) to analyse the relationships between the characteristics of tourists visiting Amsterdam, the importance they attach to different kinds of information contents available on the Internet, and the actual performance of the city as a tourism destination, measured by the expenditures and the duration of stay of the visitors. Findings indicate that the choice of e-services depends on the travel motive, age, education, income, gender, nationality, and length of stay. Furthermore, use of e-forums and virtual tours was found to significantly affect local expenditure.
Keywords: C51; M31; L83; 330; ICT; Internet; mediatisation; destination; tourism performance